Implementasi Pemenuhan Hak Tahanan dan Narapidana Lansia Dalam Pemberian Penempatan Kamar Hunian Khusus (Studi Kasus di Lapas Kelas IIB Ngawi) - Wirawan, Hendra Fikry Cindy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses vulnerable groups. Vulnerable groups are groups of people who have a high risk, where they are in situations and conditions that are considered less capable in high risk threats. Currently, what must be a concern for the government is that most prisons and detention centers have not been able to act or provide protection for vulnerable groups, focused on the elderly group. And the first two problems are taken, how is the implementation of the provision of special residential rooms for elderly Lapas Class IIB Ngawi Detention Center? This study aims to determine the implementation of the fulfillment of service rights for prisoners and convicts, to find out the implementation of the implementation of the provision of special residential rooms for prisoners and elderly prisoners, and to find out the factors that become obstacles in the implementation of the provision of special residential rooms for prisoners and elderly prisoners in Lapas Class IIB Ngawi. . This research uses a descriptive qualitative research method. Then the results of the implementation have not been fully implemented in the provision of special residential rooms for the elderly, but rooms for vulnerable groups. And some of the factors that become obstacles in providing the placement of special residential rooms for the elderly, including first, the condition of the land with dense spaces and the contents of prisoners and prisoners who are overloaded, second, consideration of the fulfillment of facilities and infrastructure, third, excess capacity, fourth, prisoners and elderly inmates do not submit complaints, and fifth, optimization of the current system.